The Diagnostic Value of Cystatin C and Mild Hypothermia Therapy Based on Immunoturbidimetry Enhanced by Nanospheres in Asphyxia Neonate - Xiaoping Dang; Xiaojian Hu; Yuancui Meng; Yan’e Yang; Lingfang Zheng; Qiong Zhang; Nan Dang; Jing Hao; Liang Zheng; Feng Ni (Journal of Chemistry)
In order to evaluate the early diagnosis value of CysC and the influence of mild hypothermia on the renal damage of asphyxia neonates, the serum cystatin C (CysC) levels of asphyxia neonates and normal neonates were measured by the nanomicrosphere-enhanced immunoturbidimetric method. The treatment was carried out, and the influence of mild hypothermia treatment on the renal damage of asphyxia neonates was analyzed. The results showed that the indicators of the asphyxia group were significantly higher than those of the control group, and the severe asphyxia group was significantly higher than that of the mild asphyxia group, which was statistically significant p<0.05; the heart rate of patients in the mild hypothermia treatment group decreased gradually with the decrease in body temperature. And compared with the control group, there was a significant difference (p<0.05); after symptomatic treatment, the two groups of ALT, AST, BUN, and SCR were improved to varying degrees, and the difference was statistically significant compared with before treatment (p<0.05). Studies have shown that serum CysC level can be used as an indicator to detect glomerular filtration function and early asphyxia newborns, and it is sensitive and specific for early diagnosis of kidney damage. At the same time, it can be used to monitor clinical renal function and determine the status of asphyxia newborns.